Prevalence and determinants of primary sclerosing cholangitis in patients with ulcerative colitis and colorectal carcinoma or dysplasia and normal liver function tests. (13th March 2011) - Culver, E L; Bungay, H K; Cummings, F J; Chapman, R W
Abstract : Introduction: Approximately 2.4–7.5% of patients with ulcerative colitis (UC) may also be diagnosed with primary sclerosing cholangitis (PSC). The risk of colorectal carcinoma (CRC) or dysplasia (CRD) has been reported to be fourfold higher in patients with PSC and UC compared to UC alone. The objective of this study is to determine the prevalence of undiagnosed PSC in UC patients with CRC or CRD. Methods: 19 patients with histologically confirmed UC and CRC or CRD, with normal liver function and no prior imaging suggestive of PSC were identified. Patients had a magnetic resonance cholangiogram (MRC) and blood tests taken for pANCA, ANA, IgG and subclasses and HLA typing. Medical case notes, laboratory data and endoscopic records were reviewed retrospectively. MRCs were obtained from 21 healthy volunteers and 22 patients with established PSC to act as negative and positive controls, respectively. The Student's t test and χ 2 test were used for analysis where appropriate. Results: 26 patients met the inclusion criteria, of which 19 patients were recruited. The median age was 67 years (range 52–87) with a male predominance (74%). 15 patients (79%) had extensive and 4 (21%) left-sided colitis. Two patients (10%) had CRC, 6 (32%) high-grade and 11 (58%) low-grade CRD. 17 patients (89%) had CRC or CRD in the left colon. Two out of 19 patients (10%) had biliary abnormalities consistent with PSC on MRC. All 21 healthy volunteers had no evidence of PSC on MRC. All 22 PSC patients had characteristics of PSC on MRC. Both patients with evidence of PSC had a quiescent pancolitis and a mild disease course, with no acute admissions, immunosuppressive or biological therapy for colitis. One patient had high-grade CRD and the other CRC in the left colon. Neither patient had a positive pANCA or ANA. One had HLA haplotypes known to be associated with PSC as well as a raised IgG and IgG4. There was no difference between the median ages, duration of IBD, family history or presence of extra-intestinal manifestations of the two groups. No patient has had a liver biopsy. Conclusion: This small study of patients with UC and CRC or CRD and normal liver function has demonstrated unsuspected biliary abnormalities consistent with PSC on MRC, in 2 of 19 patients. Previous work in our group has suggested a comparable prevalence of PSC in patients with extensive UC and normal LFTs.1 Larger studies are required to explore the relationship between possible undiagnosed PSC and the development of CRC/CRD in IBD patients. This may help to stratify screening strategies in the future.